Development and validation of a new performance‐based measurement of instrumental activities of daily living in Taiwan. Issue 4 (17th December 2014) - Chen, Hui‐Mei; Yeh, Yi‐Chun; Su, Wei‐Lieh; Huang, Mei‐Feng; Chang, Chun‐Wei; Chen, Cheng‐Sheng
Abstract: Background: The performance‐based instrumental activities of daily living (IADL) measurement is thought to improve the validity and reliability of conventional tools that rely on proxy reports. The aims of this study were to develop and validate a performance‐based measurement of IADL for use in elderly patients with cognitive impairment in Taiwan and other Chinese‐speaking communities. Methods: Referring to current versions of performance‐based IADL, we developed the new Taiwan Performance‐Based IADL (TPIADL) measurement to minimize literacy dependency and render it compatible with local culture. Participants performed tasks, including finding a telephone number, calculating the correct amount of change, reading the ingredients on a tin of food, finding food items on a shelf, and reading instructions on a medicine container. The internal consistency and convergent and criteria validity of the TPIADL were examined. Results: Altogether, 117 elderly subjects were invited to participate in this study, including 39 patients with dementia due to Alzheimer's disease, 29 with amnestic mild cognitive impairment, and 49 without cognitive impairment. The internal consistency of the TPIADL was 0.82. The TPIADL scores were significantly correlated with the Lawton Instrumental Activities of Daily Living Scale ( r = 0.76, P < 0.001). The area under the relative operating characteristic curve was 0.90 (95% confidence interval = 0.84–0.97) to differentiate dementia due to Alzheimer's disease and others. The optimal cut‐off point for the TPIADL was 6/7, which gives a sensitivity of 84.6% and a specificity of 75.6%. Conclusions: The TPIADL is a validated instrument for the measurement of IADL in elderly subjects. It might replace conventional assessment as a valid and easily administered measurement.